Clinicopathological diversity of semantic dementia: Comparisons of patients with early‐onset versus late‐onset, left‐sided versus right‐sided temporal atrophy, and TDP‐type A versus type C pathology. Issue 1 (6th November 2022) - Kawakatsu, Shinobu; Kobayashi, Ryota; Morioka, Daichi; Hayashi, Hiroshi; Utsunomiya, Aya; Kabasawa, Takanobu; Ohe, Rintaro; Futakuchi, Mitsuru; Otani, Koichi
Abstract : Semantic dementia (SD) is a unique clinicopathological entity associated with TDP‐type C pathology. We present four cases of SD that illustrate the clinicopathological diversity of TDP‐43 pathology, including early‐onset cases of TDP‐type C with corticospinal tract (CST) and motor neuron pathology and late‐onset cases of TDP‐type A with combined pathology. Case 1 was a 62‐year‐old man with semantic variant of primary progressive aphasia (svPPA) with left‐predominant temporal atrophy and TDP‐type C pathology with low Alzheimer's disease neuropathologic changes (ADNC). Case 2 was a 63‐year‐old woman with right‐predominant temporal atrophy and TDP‐type C pathology who had prosopagnosia and personality changes. Phosphorylated(p)‐TDP‐43‐positive long dystrophic neurites (DNs) were observed throughout the cerebral cortex; they were more abundant in the relatively spared cortices and less so in the severely degenerated cortices. We observed CST degeneration with TDP‐43 pathology in the upper and lower motor neurons, without apparent motor symptoms, in SD with TDP‐type C pathology. Case 3 was a 76‐year‐old man who had svPPA and personality changes, with left‐predominant temporal atrophy and TDP‐type A pathology with high ADNC and argyrophilic grain (AG) stage 3. Case 4 was an 82‐year‐old man who had prosopagnosia and later developed symptoms of dementia with Lewy bodies (DLB) with right‐predominant temporal atrophy and TDP‐type A pathology with high ADNC, DLB of diffuse neocortical type, and AG stage 3. The distribution of p‐TDP‐43‐positive NCIs and short DNs was localized in the anterior and inferior temporal cortices. An inverse relationship between the extent of TDP pathology and neuronal loss was also observed in SD with TDP‐type A pathology. In contrast, the extent of AD, DLB, and AG pathology was greater in severely degenerated regions. CST degeneration was either absent or very mild in SD with TDP‐type A. Understanding the clinicopathological diversity of SD will help improve its diagnosis and treatment.